(untitled) (Research, Society and Development, 2021)
Payment for Environmental Services became law (14,119/21) in 2021, so a milestone is installed in the treatment of relevant environmental aspects. In this context, the quality of environmental information must be seen as a business language at the international level. Therefore, this research seeks to investigate: it seeks to understand the typological alignment applied in the texts of Law 14.119/21 in relation to the theoretical framework on the IFRS standard that deals with fair value: Fair value CPC 46 - Fair Value Measurements (financial instruments); IFRS 13 Fair Value Measurement and Biological Assets (Plants and Animals) CPC 29 - IAS 41. For methodology, case studies were used with Klabin SA as the object and an analysis of the document type was also carried out in the text of the Payment Law environmental services (PSA) and the quarterly report of a potentially polluting company in the pulp and paper segment. Through the discussions and the results, it was possible to verify that some aspects related to financial information (fair value and market value) were not taken into account in the wording of the aforementioned Law. It was also observed that the PES Law outlines more environmental issues than those observed by the company in question.